2021
DOI: 10.1002/pssa.202100073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Al2O3 and HfO2 for Surface Passivation of Cu(In,Ga)Se2 Thin Films: An Innovative Al2O3/HfO2 Multistack Design

Abstract: In Cu(In,Ga)Se 2 (CIGS) thin-film solar cells, interface recombination is one of the most important limiting factors with respect to device performance. Herein, metal-insulator-semiconductor samples are used to investigate and compare the passivation effects of Al 2 O 3 and HfO 2 at the interface with CIGS. Capacitance-voltage-frequency measurements allow to qualitatively and quantitatively assess the existence of high negative charge density (Q f % À10 12 cm À2 ) and low interface-trap density (D it % 10 11 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…[ 22 ] Based on these results, we conclude that both TaO x (on CZTSSe) and HfO 2 (on CIGS) are sustainable in the CBD solution. Therefore, TaO x –Al 2 O 3 or even TaO x –other insulating bilayers can be a viable route for engineering the passivation materials, which can protect Al 2 O 3 (or the chemically unstable insulating layer during the CBD process) from the attack of the chemical bath solution to maintain and even modify the interface quality of Al 2 O 3 (or the insulating layer)–CZTSSe, based on the HfO 2 ‐insulating bilayers proposed by Scaffidi et al [ 40 ] Moreover, TaO x is often connected with SiN x to reach its best passivation quality and carrier transport as an electron selective contact or passivation layer for Si solar cells. [ 23 ] Therefore, the passivation properties of TaO x may be improved by nitrogen doping, or annealed in a hydrogen atmosphere, which offers more opportunity for TaO x as a passivation layer for further improved efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 ] Based on these results, we conclude that both TaO x (on CZTSSe) and HfO 2 (on CIGS) are sustainable in the CBD solution. Therefore, TaO x –Al 2 O 3 or even TaO x –other insulating bilayers can be a viable route for engineering the passivation materials, which can protect Al 2 O 3 (or the chemically unstable insulating layer during the CBD process) from the attack of the chemical bath solution to maintain and even modify the interface quality of Al 2 O 3 (or the insulating layer)–CZTSSe, based on the HfO 2 ‐insulating bilayers proposed by Scaffidi et al [ 40 ] Moreover, TaO x is often connected with SiN x to reach its best passivation quality and carrier transport as an electron selective contact or passivation layer for Si solar cells. [ 23 ] Therefore, the passivation properties of TaO x may be improved by nitrogen doping, or annealed in a hydrogen atmosphere, which offers more opportunity for TaO x as a passivation layer for further improved efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used for the characterization of the Q f and D it between CIGS and an oxide layer. [39,40] C-V measurements were conducted for the MOS structure of the kesterite film with 20 nm TaO x , depicted in Figure S11a, Supporting Information, to characterize the interface properties of TaO x -CZTSSe. A sufficient thick oxide layer (20 nm) was used here to prevent potential dielectric leakage or tunneling effect, which may significantly affect the analysis of C-V measurements.…”
Section: Characterization Of Kesterite Solar Cells With Point Contact...mentioning
confidence: 99%
“…For CIGSe this has been done using AlO x and HfO x passivation layers. [ 22,24,25 ] The D it values determined from CV measurements were somewhere between 10 11 and 10 12 eV −1 cm −2 . This is a moderate reduction of interface defects, but not enough to reduce the effective lifetime to 100 cm s −1 .…”
Section: Passivation Schemes Of Cigsementioning
confidence: 99%
“…Studies based on absorber/passivation structures have revealed passivating properties showing the potential of dielectric passivation of the front surface. [ 21–25 ] Though, to date no improvements in solar cells have been observed. [ 26–32 ] Often fill factor (FF) losses and problems with current extraction arise.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] Moreover, several oxide materials, such as SiO x , GaO x , HfO 2 , and TiO 2 have been introduced to the CIGS thin film solar cells. [39][40][41][42][43][44][45][46][47] Among them, TiO 2 was one of the passivating contacts which has been widely applied to c-Si solar cells. [36,48] While for CIGS solar cells, TiO 2 was usually deposited on top of CdS layer as the capping layer to avoid shunt and sputtered damage, or replace the CdS layer as the buffer layer, and it has scarcely any reports that the interface of CdS/CIGS as the tunneling layer up till now.…”
Section: Introductionmentioning
confidence: 99%